Nietzsche's Human, All Too Human - Abbey, Ruth (Edinburgh Critical Guides to Nietzsche : ECGN, 2022)
A critical introduction and guide to one of Nietzsche's pivotal but lesser-known textsDevotes a chapter to each of Human, All Too Human's 9 chapters, plus a chapter each on 'Assorted Opinions and Maxims' and one on 'The Wanderer and Its Shadow' - originally published as separate worksAssumes no prior knowledge or Nietzsche or Human, All Too HumanContextualises Human, All Too Human in Nietzsche's philosophyIncludes a chronology of Nietzsche's life and work, a glossary of key terms, an index of names and subjects and a guide to further readingHuman, All Too Human marks the beginning of what is often called Nietzsche's middle or positivist period (which ends with the conclusion of Book IV of The Gay Science). It initiates some important features that become permanent in his work, such as his experiments in multiple writing styles within one work, his self-representation as a psychologist, his genealogical excavations of morality and his appeal to fellow Europeans to overcome the parochialism and antagonism of nationalism.Ruth Abbey shows Nietzsche to be more receptive to the Enlightenment tradition than he is typically taken to be. She assumes no knowledge of the text or of Nietzsche. She maps her chapters onto those of Nietzsche's text, allowing you to read the guide alongside the book. Altogether, she opens up Human, All Too Human for new readers, while more experienced Nietzsche scholars will appreciate the new perspective